KONSEPTUALISASI LOYALITAS KERJA TERHADAP KINERJA KARYAWAN PADA GENERASI MILLENIAL DI PT.PLN INDONESIA POWER KAMOJANG POMU - Wulan Utami; Ramayani Yusuf; Hendriady de Keizer (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2023)
Good human resources is one of the organizational functions that must be owned so that the performance of the organization or company runs well. This study aims to analyze the conceptualization of work loyalty on employee performance in generation millenial at PT.PLN Indonesia Power Kamojang POMU. The data collection method used was by distributing questionnaires, samples and the population used was 50 generation millenials employees with an age range of 25-35 years. technical data analysis used in this study is to use a quantitative descriptive method, where this method aims to explain or describe the characteristics of a state of the object of research. This study uses a simple linear regression test analysis, classical assumption test. The analytical tool used is SPSS. The variables used consist of independent variables, namely work loyalty and the dependent variable, namely employee performance. Based on the results of the study, it can be interpreted that work loyalty has a positive and significant effect on employee performance at PT.PLN Indonesia Power Kamojang POMU, which means that if work loyalty increases, the resulting employee performance will also increase. Important information from this study is that work loyalty affects performance, so companies need to pay attention to this.